0731 Obstructive Sleep Apnea with Predominant Respiratory Effort Related Arousals: Theta Power in C3- M2 And C4-M1 Derivation Comparison in Male And Female. (27th May 2020) - Hura, K; Singh, H; Sahota, P; Thakkar, M
Abstract: Introduction: Theta power in electroencephalography has been studied as a correlate to REM sleep. An increase in theta power during REM sleep has been observed in patients during recovery sleep after sleep deprivation. Emotional memories appear to be processed and consolidated during REM sleep.The role of hippocampal theta wave activity during REM sleep on emotional memory processing is limited. The importance of theta power has not been well characterized in patients with obstructive sleep apnea (OSA) with predominant respiratory Effort Related Arousals (RERAs). This report aims to study the theta power in patients with OSA with predominant Respiratory Effort Related Arousals (RERAs) with an apnea-hypopnea index (AHI) of < 5. Methods: We have identified 38 patients with baseline polysomnograms performed from December 2019 to July 2019 with AHI < 5 and a Respiratory Disturbance Index (RDI) of at least 5 or greater. Patients with chronic hypoxemic respiratory failure, hypoventilation and predominant central sleep apnea were excluded from the study. Total power of frequency in bands was obtained for theta waves (4-8 Hz) and total waves (1-30 Hz). Relative theta power was calculated on the last REM sleep using C3-M2 and C4-M1 derivations. Paired two-tailed t-Test was performed on the theta power in C3-M2 and C4-M1 in both the sexes. Results: Initial analysis was performed in 38 patients out of which 20 were male and 18 female. Among males, (Mean ± SEM) age was 52.3 (±2.9); Epworth Sleepiness Scale (ESS) of 6.6 (±1.1), AHI of 2.1 (±0.3), and RDI of 7.3 (±0.3).Whereas in female (Mean ± SEM) age was 46.8 (± 2.8), ESS of 7.7 (±1.4), AHI of 2.3 (±0.35), and RDI of 6.9 (±0.4). Statistically significant difference was noted in the theta power between the C3-M2 and C4-M1 derivations with P value of 0.03 and 0.04 in male and female respectively. However, no significant difference was found when C3-M2 and C4 -M1 was compared between male and female. Further, statistical analysis will be performed after gathering data from a larger sample size. Conclusion: There was significant difference between C3-M2 and C4-M1;overall no difference was found between sexes. Support: none